Epistemology in university research - Zeña Quépuy, Carlos (2015)
This essay focuses on the urgent need to incorporate the epistemological management in university researches, understanding Epistemology as the Philosophy of Science in the development of diagnostic research that in the pre factual stage, determine the proliferation of regrettable positivist positions that cancel the philosophical approach, it means the subjective position and the dialectical position of the researcher. The revision about educational researches of undergraduate and postgraduate levels, in several virtual and physical libraries, lets to verify the positivist dogmatism; validation of the instrument, expert judgment, pilot test, measures of central tendency, validity and quantitative reliability and elementary data interpretation. This is not the valid, objective and scientific essence of the university research.